Electrical Transport and Related Dielectric Phenomena in Coconut-Shell Activated Carbon - W. Yusoff, W. Mohamad Daud (1991)
The electrical properties of coconut-shell activated carbon have not been thoroughly investigated and are, therefore, not well understood. In order to study these properties meaningfully, a fairly satisfactory knowledge of the structure, microstructure and composition of the material is needed. Since the material's constitution has been little studied and dealt with in the relevant published literature, investigation of the structure and composition of the material has to be done in a comprehensive manner.The experimental investigation is divided into two categories. Firstly, the basic experimental work, which is considered important in order to provide supportive evidence to any proposed model of charge-carrier conduction and dielectric behaviour, consists of work on x-ray diffractome try, neutron activation analysis, Fourier transform infra-red spectroscopy, scanning electron microscopy, thermoelectric power and magnetoresistance. Secondly,the main experiments consist of work on direct current conductivity and alternating current conductivity measurement.